The Impact of Social Media Marketing for MSMEs Sustainability in Covid-19 Period - I Gusti Agung Ayu Mas Suariedewi; I Wayan Chandra Adyatma; I Gusti Ayu Athina Wulandari (Journal of Business and Management Review, 2022)
The Covid-19 pandemic impacts small and medium enterprises (MSMEs) performance in production, marketing, and income, especially in Denpasar City. MSMEs experienced a decline in the level of demand and supply during the implementation of social distancing policies. The role of social media can help in the conditions of the Covid-19 pandemic. In this case, it can be said that social media can help the economy of MSMEs in business activities. This study aims to analyze the factors that use social media marketing, namely perceptions of ease of use, perceived usefulness, cost, and influence on MSMEs. The study was conducted on MSMEs owners in Denpasar City who sell food, beverages, services, and fashion. Data were collected utilizing research questionnaires which were distributed to 100 respondents. The data analysis technique used SEM-PLS (Structural Equation Modeling-Partial Least Square) with Smart PLS 3.0. The results showed that Perceived Usefulness had a positive and significant effect on social media marketing. Perceived Usefulness has a positive and significant effect on the SMEs sustainability. Perceived ease of use has a positive and significant effect on social media marketing. The cost has a positive and significant effect on social media marketing. Social media marketing has a positive effect on MSMEs. However, costs have no impact on MSMEs. Based on the results of the VAF test, social media marketing acts as a partial mediating variable between perceived Usefulness and perceived ease of use for MSMEs sustainability.